2020
DOI: 10.1177/1464884920924527
|View full text |Cite
|
Sign up to set email alerts
|

‘We are a neeeew generation’: Early adolescents’ views on news and news literacy

Abstract: To function as well-informed citizens in democracy, early adolescents (12–16 years old) should become news literate news consumers. In this time of fragmented media use and evolving conceptions of (the importance and relevance of) news, this is not easy. Therefore, this focus group study investigated news consumption and news literacy through the eyes of early adolescents. Results showed that early adolescents have broad definitions of news. Their news consumption is predominantly passive, possibly due to a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 31 publications
2
38
0
1
Order By: Relevance
“…Teenage participants also discussed the verification of online content found through Google, with one participant saying that they ‘check the byline and see who has written an article’ (Lena-16). Others reported that they used “content-specific strategies” (Tamboer et al 2020: 12) which includes checking sources or links as well as the writing style of a news item. In general, the young people from the focus groups placed importance on a range of features when determining which content is reliable, most of which relates to the strategies identified by Swart and Broersma (2021: 9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Teenage participants also discussed the verification of online content found through Google, with one participant saying that they ‘check the byline and see who has written an article’ (Lena-16). Others reported that they used “content-specific strategies” (Tamboer et al 2020: 12) which includes checking sources or links as well as the writing style of a news item. In general, the young people from the focus groups placed importance on a range of features when determining which content is reliable, most of which relates to the strategies identified by Swart and Broersma (2021: 9).…”
Section: Resultsmentioning
confidence: 99%
“…Studies among teenagers and young adults point to a change in the understanding of journalism as a professional news source. Qualitative work suggests that teenagers have broad definitions referring to important and relevant topics (Tamboer et al 2020) whereas young adults’ idea of news is characterised by traditional genre conventions (Kümpel 2020). Besides, discrepancies between news definitions and the use practices of young people persist (Craft et al 2016).…”
Section: Journalism Young People and News Use In A Hybrid Media Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Fallis, 2015; Søe, 2017, 2021), as well as on, for example, automatic recognition of false information. Other closely related topics of interest are those of news (Ireland, 2018; Tamboer et al , 2020), media (Jones-Jang et al , 2021; Stamps, 2020) and information (Gibson and Jacobson, 2018; Jacobson and Mackey, 2013) literacy. Although fact-checking, false information and literacy research are related topics, this study focuses explicitly on fact-checking as a human practice rather than on what constitutes a fact, or mis- and disinformation.…”
Section: Literature Reviewmentioning
confidence: 99%